Solid-Liquid Interfacial Energy of Solid Succinonitrile in Equilibrium with Succinonitrile-(D) Camphor-Aminomethylpropanediol Eutectic Liquid - Ata, Pinar; Karamazi, Yasin; Bayram, Umit; Aksoz, Sezen; Keslioglu, Kazim; Marasli, Necmettin (SPRINGER/PLENUM PUBLISHERS, 2016)
The grain boundary groove shapes for equilibrated solid SCN in equilibrium with the eutectic liquid SCN-15.6 mol% DC-2.1 mol% AMPD have been directly observed by using a horizontal linear temperature gradient apparatus. The ratio of the thermal conductivity of the equilibrated liquid to the thermal conductivity of solid SCN has also been determined to be 0.89. From the observed grain boundary groove shapes and measured thermal conductivity ratio, the Gibbs-Thomson coefficient (Gamma), solid-liquid interfacial energy (sigma(SL)), and the grain boundary energy (sigma(gb)) have been determined to be (5.43 +/- 0.54) x 10(-8) K.m, (8.53 +/- 1.28) x 10(-3) J.m(-2), and (13.36 +/- 2.14) x 10(-3) J.m(-2), respectively, for equilibrated solid SCN in equilibrium with the eutectic liquid (SCN-15.6 mol% DC-2.1 mol% AMPD).
Keywords: Interfaces; Organic compounds; Phase equilibria; SURFACE ENERGIES; PIVALIC ACID; ORGANIC ALLOYS; AL-CU; SYSTEMS; METALS; MELT; ANISOTROPY; GROWTH; SOLIDIFICATION; Thermodynamics; Chemistry; Mechanics; Physics